2010
DOI: 10.3382/ps.2009-00207
|View full text |Cite
|
Sign up to set email alerts
|

Performance and antioxidant status of broiler chickens supplemented with dried mushrooms (Agaricus bisporus) in their diet

Abstract: In this study, we evaluated the growth performance and antioxidant status of broiler chicken supplemented with the edible mushroom Agaricus bisporus. Ninety 1-d-old female broiler chickens randomly allotted to 3 dietary treatments were given either a nutritionally balanced basal diet or the basal diet supplemented with 10 or 20 g of dried mushroom/kg of feed for 6 wk on an ad libitum basis. Body weight, feed intake, and feed conversion ratio values were monitored weekly. To evaluate the antioxidant status of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
73
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 56 publications
12
73
1
2
Order By: Relevance
“…This difference indicates that both supplementation levels were associated with the highest free-radical sequestration capacity due to the higher concentration of antioxidant compounds present in the meat, resulting in tissue preservation of the animal in vivo. Phenolic compounds of low molecular weight, despite their low liquid absorption in the intestine, reach the bloodstream and promote antioxidant activity in animals (GIANNENAS et al, 2010). After five days of cooling, the residual antioxidant capacity in meat to sequester the free radical DPPH was reduced (P < 0.05) compared with day 0.…”
Section: Ablazei (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…This difference indicates that both supplementation levels were associated with the highest free-radical sequestration capacity due to the higher concentration of antioxidant compounds present in the meat, resulting in tissue preservation of the animal in vivo. Phenolic compounds of low molecular weight, despite their low liquid absorption in the intestine, reach the bloodstream and promote antioxidant activity in animals (GIANNENAS et al, 2010). After five days of cooling, the residual antioxidant capacity in meat to sequester the free radical DPPH was reduced (P < 0.05) compared with day 0.…”
Section: Ablazei (%)mentioning
confidence: 99%
“…Using Agaricus bisporus in the diet of broilers and turkeys, Giannenas et al (2010Giannenas et al ( , 2011 observed, after five days of refrigeration, the presence of a higher content of malondialdehyde as a result of lipid oxidation in the meat of birds without supplementation compared with birds supplemented with the mushroom. It has been suggested that antioxidant activity is dose dependent and that the protective effect of A. bisporus is a result of the ability of fractions of polysaccharides and polyphenols to stabilize free radicals by electron transfer.…”
Section: Ablazei (%)mentioning
confidence: 99%
“…Amongst meat products, poultry meat is considered to be more prone to the development of oxidative rancidity compared to red meat (Ali & Zahran, 2010) due to the higher content of phospholipids in poultry meat. Lipid peroxidation and microbial spoilage are the leading causes of meat quality deterioration affecting color, flavor, texture, and nutritional value (Giannenas et al, 2010;Jayawardana, Liyanage, Lalantha, Iddamalgoda, & Weththasinghe, 2015). Thus, controlling microbial contamination and oxidative peroxidation during poultry meat product preparation and processing is of great importance for both consumers and meat processors.…”
Section: Introductionmentioning
confidence: 99%
“…Giannenas et al (2010) reported that A. bisporus has a prebiotic-like effect on turkeys since fermentable polysaccharide content in mushrooms may improve growth of Lactobacilli and Bifidobacteria populations and inhibit E. coli leading to a more balanced biota population in the gastrointestinal tract of poultry, as a consequence, to a greater efficiency in digestibility and feed utilization. Furthermore, Lactobacilli may produce organic acids such as lactic acid (Rehman et al, 2007) and bactericidal substances (Neal-McKinney et al, 2012) that may improve gastrointestinal function and feed digestibility, resulting in enhanced growth and improved FCR (Ferket, 2004).…”
mentioning
confidence: 99%